AL HAJAWI HADITH'S LOCAL WISDOM THOUGHTS : (Study of the Sekar Cempako Poetry Manuscript) - Hendri Waluyo Lensa; Siti Nazla Raihana; Salsabila Fagih (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
One form of the local wisdom of the archipelago's ulamas in grounding the noble values of Islamic religious teachings, is the dissemination of the concepts and content of the hadiths of One form of local wisdom of the archipelago's scholars in grounding the noble values of Islamic teachings is the dissemination of the concepts and content of the traditions of the Prophet Muhammad ﷺ in Javanese language, modified with Arabic style and written in beautiful poetic strokes. The combination of these concepts is considered cooler, more interesting, and more familiar to the ears and souls of those who receive it from the Javanese community. This study aims to explore the concept of hadith thought of Abu Muhammad Al Hajawi and to determine the quality of the hadiths that are expressed in the form of Sekar Cempoko poems. The data analysis technique in this research is content analysis, in which researchers study and analyze the concept of Al Hajawi's hadith thinking. The results of this study show that Al Hajawi conveys the noble values of the prophet's traditions not with the original text but by translating them into the language of the local community and then making them more attractive by decorating them with literary art in the form of poems. As for the typology of the quality of the traditions that are highlighted in his verses in this manuscript, not all of them are categorized as sahih and hasan, there are some weak and even false hadith that he implies in some of his verses.